DETERMINANT ANALYSIS OF LOCAL RETRIBUTION ON LOCAL REVENUE - Rina Setyawati; Sitti Retno Faridatussalam (SEAN Institute, 2023)
Retribution functions as a natural source of income for the region, as a budget to finance all daily government needs, and also helps in regional development. If the budget is sufficient, all economic activities can run well. The purpose of this study was to determine the effect of building permit fees, cleaning fees, parking fees, motor vehicle inspection fees, and costs of using the regional property on the main regional income. The survey was conducted in 26 provinces/cities in Central Java during the 2019-2021 period. This survey method uses panel data regression and is estimated using Eviews 10. The study shows that the FEM estimate was chosen as the best estimate. Cleaning fees, building permit fees, and some parking fees have a positive impact on local revenues. On the other hand, from 2019 to 2021, in 26 regencies/cities in Central Java, BUMN PPh and PKB Tax have no impact on local revenue